THE POSTPYLORIC NUTRITION SUPPORT IN THE COMPREHENSIVE TREATMENT OF THE NEONATAL SEPSIS - R. Kh. Gizatullin; P. I. Mironov (Вестник анестезиологии и реаниматологии)
The study was undertaken for the relationship of the transpyloric jejunal nutrition support in infants suffering from severe sepsis and the long-lasting gut-specific malfunction. The study design is retrospective, probationary, single-center, historical control. A total of 127 infants were examined. The inclusion criteria are: neonatality, the available focus of inflammation infection, the dysfunction of two and more systems, the artificial pulmonary ventilation longer than 48 hours, available enteroparesis, ≥ 3 scores by the PRNS scale. It was established that under development of the intestinal failure with the sepsis infant patients, the transpyloric pathway is the preferred one for the enteral feeding delivery. The indication for the installation of the jejunal enteral feeding tube is the volume of the venter stagnant discharge of > 6 ml per day.